2013
DOI: 10.1186/1471-2369-14-177
|View full text |Cite
|
Sign up to set email alerts
|

Body mass index and metabolic factors predict glomerular filtration rate and albuminuria over 20 years in a high-risk population

Abstract: BackgroundThe number of individuals suffering from chronic kidney disease (CKD) is increasing. Therefore, early identification of modifiable predictors of CKD is highly desirable. Previous studies suggest an association between body mass index (BMI), metabolic factors and CKD.MethodsData of 241 high risk patients with information on renal function and albuminuria from the Renal Disease in Vorarlberg (RENVOR) study (2010–2011) were linked with long-term measurements of metabolic factors in the same patients fro… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

4
15
1

Year Published

2015
2015
2020
2020

Publication Types

Select...
9

Relationship

1
8

Authors

Journals

citations
Cited by 20 publications
(20 citation statements)
references
References 36 publications
4
15
1
Order By: Relevance
“…This result is in agreement with that that of a study by Nagel et al (2013), which found no relationship between the BMI and albuminuria in women. It is in contrast to that of a study by Metcalf et al (1992).…”
Section: Bmi and Urinary Albumin Levelssupporting
confidence: 83%
“…This result is in agreement with that that of a study by Nagel et al (2013), which found no relationship between the BMI and albuminuria in women. It is in contrast to that of a study by Metcalf et al (1992).…”
Section: Bmi and Urinary Albumin Levelssupporting
confidence: 83%
“…The gamma‐glutamyl transpeptidase data point to associations with liver disorders, which attract a default diagnosis of (sometimes non‐alcoholic) fatty liver. This association, which is insufficiently explored in the Australian context, is supported by other regional and international studies and is generally said to mark the metabolic syndrome and insulin resistance . In that Australian Health Survey (AHS) survey, CKD in indigenous people was also associated with anaemia and with higher triglyceride levels, but not with high total or low‐density lipoprotein cholesterol levels.…”
Section: Introductionmentioning
confidence: 98%
“…But several studies showed that GGT was predictor of microalbuminuria and long-term predictor of renal function. [8][9][10] As a prognostic marker for nephropathy, albuminuria has been shown to correlate with structural and dysfunctional of the vasculature. 11 In addition, serum GGT level is associated with vascular endothelial dysfunction which leads to urinary albumin extraction in patients with kidney disease.…”
Section: Discussionmentioning
confidence: 99%